Studi konsumsi energi sebagai kajian awal untuk mengetahui & memonitor efisiensi penggunaan energi - Ghurri, Ainul; Putra Wibawa, Ngurah; Widjaksana, Hendra (Jurnal Energi Dan Manufaktur; Vol 1, No.2 Desember 2006, 2012)
Investigation on energy consumption is early step to monitor energy consumption and efficiency. Assessment on energy consumption is aimed to investigate how much energy has been consumed by a company, a region or a country. The growth of energy consumption can show the economic and welfare improvement. From the total energy consumed we can then break down it to the sectors of energy user, e.g. transportation, industry, commercial building, etc. By comparing the total energy consumed to the benefits of energy consumption we can predict the energy efficiency. This research is still early stage and just covers the energy consumption by Balinese society. The fuel and energy consumption by Balinese society was analyzed based on the data from Pertamina branch Denpasar. It was found that the biggest fuel consumed is solar, followed by premium-premix, minyak tanah, LPG, avtur, and avgas, respectively. During 1998 to 2003 the Balinese’s energy consumption increased gradually with changeable fluctuation from 56.63 Peta Joule to 80.53 Peta Joule. The biggest rise was happened in 1999-2000, i.e. 16.43%, and the lowest rise was happened in 2002-2003, i.e. 0.9%. Transportation was the biggest consumer of the Balinese energy, i.e. 69.21% in 2000 and 71.03% in 2001. In order to investigate the energy efficiency, it was found that the energy users have not been used the energy intensity as indicator yet to measure their energy efficiency. Some no uniformity in data classification and the unavailability data caused this research can’t be conducted more precise and detail yet.
Keywords: Energy consumption, energy efficiency